Ancient worlds modern beads - VanPelt, Mortira Natasha (kent, England Search Press, 2015)
30 beadweaving designs combining new and traditional techniques with popular classical themes inspired by ancient Rome, Greece and Egypt. Projects range in skill level from easy to advanced, appealing to the novice and experienced beader alike
2 13
Keywords: Beaded jewelry; Beadwork; Jewellry making